2003
DOI: 10.1007/s00381-003-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of corpus callosum: prenatal diagnosis and prognosis

Abstract: This study demonstrates that if outcome of isolated ACC is favorable, a long follow-up is necessary: with age, IQ in the lower range and behavioral troubles are linked to difficulties in school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
95
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 16 publications
7
95
0
3
Order By: Relevance
“…A definitive diagnosis of ACC relies on recognition of the direct signs (Pilu et al, 1993;Moutard et al, 2003;D'Addario et al, 2005), which consist of the demonstration of the absence of the CC on mid-sagittal and coronal views of the fetal brain. In particular, the mid-sagittal plane will demonstrate absence of the CC and, in advanced gestation or post-natally, an atypical radiating appearance of the median sulci, which converge toward the third ventricle ( Figure 6).…”
Section: Sonographic Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…A definitive diagnosis of ACC relies on recognition of the direct signs (Pilu et al, 1993;Moutard et al, 2003;D'Addario et al, 2005), which consist of the demonstration of the absence of the CC on mid-sagittal and coronal views of the fetal brain. In particular, the mid-sagittal plane will demonstrate absence of the CC and, in advanced gestation or post-natally, an atypical radiating appearance of the median sulci, which converge toward the third ventricle ( Figure 6).…”
Section: Sonographic Findingsmentioning
confidence: 99%
“…Prognosis: Although the overall prognosis of ACC remains controversial, several studies have reported a worse prognosis in the presence of additional anomalies (Shevell et al, 2002;Moutard et al, 2003;Volpe et al, 2006). In fact ACC is often associated with major cerebral and/or extracerebral malformations, including 50 different human congenital syndromes, and metabolic diseases (Tables 1, 2, 3, 4).…”
Section: Sonographic Findingsmentioning
confidence: 99%
See 3 more Smart Citations